Factors influencing visitor satisfaction at selected caves in Slovakia - Pančíková, Kristína; Veselovský, Ján; Beták, Norbert (Turyzm/Tourism, 2025)
This study aims to identify and evaluate the factors influencing visitor satisfaction in selected caves in Slovakia, with a particular focus on their relative importance and impact on overall satisfaction. A survey was conducted with 400 respondents – visitors to six caves managed by the Slovak Caves Administration. The analysis employed the importance-performance analysis (IPA) method alongside importance and satisfaction indices to assess objective satisfaction factors. These factors were ranked using the Friedman and Wilcoxon test, while relationships between subjective factors and satisfaction were examined through non-parametric methods, including Spearman’s correlation coefficient, the Mann-Whitney U test and the Kruskal-Wallis test. Ordinal logistic regression was used to determine the combined influence of objective and subjective factors on overall visitor satisfaction. The results indicate that several objective factors significantly affect satisfaction: group size during a tour, the tour route itself, cleanliness of exterior and entrance areas, cave location and accessibility, souvenir shop services, quality of the guide’s commentary and parking facilities. Among subjective factors, only the organization of the visit showed a statistically significant effect on overall satisfaction. These findings offer valuable insights for the strategic management and development of speleological tourism in Slovakia and may support efforts to enhance the competitiveness of Slovak caves on both domestic and international tourism markets.